Achievement of High-Performance Goals of Export Industry in Thailand through Quality Management Tool of Supply Chain Management - Duangsamorn Rungsawanpho; Sittichai Thammasane (International Journal of Supply Chain Management, 2019)
This study examined how high-performance goals can be achieved by the export firm of Thailand by providing high-quality products to their customers with the help of an effective supply chain (SC) practices. Data were collected from the exports mangers of all exporting firm that are currently operating in Thailand. Multiple regression and bootstrapping techniques are used to investigate the relationships under study variables by using PLS-SEM. The results indicated that effective SC practices could improve the quality of the products that help in achieving the high-performance goals of the organization. This study also suggested to the policymakers that they should adopt quality measures to enhance the quality of the product; because the quality products are able to accept the challenges of global competition that result in high performance of the firm.